How Does Aesthetics Express Itself? Deleuze, from the Imperceptible to the Affects - Perotto, Francesca (Aesthetica Preprint, 2023)
To overcome the traditional representative conception of aesthetics, inhibiting the creative and disruptive power of the sensible, while relegating its creativity to artistic activity, Deleuze proposes an expressive account of sensibility, conceived as an intensive field of individuation that expresses itself through affectivity. The article will retrace the essential passages of this operation, from the establishment of an intensive domain of individuation in early transcendental empiricism to the radical short-circuit of anthropocentrism in his late constructivism. Moving from the paradox of the imperceptible, particular attention will be paid to the Deleuzian conception of the affects, the peak of the radicalization of his aesthetic proposal. It will be argued how it offers a fundamental link to an ethics of power, making the limits of the discipline implode.